International Tariff Relations as Affected by the War - Culbertson, W. S. (Quarterly Journal of Economics, 1918)
I. Tariff discriminations, 547. — Classes of discriminations, 548. — II. Discriminations and bargaining, 549. — Penalty duties, 549. — Bargaining systems, 551. — Most-favored-nation clause, 552. — III. Discriminations based on national policies, 555. — American experiences, 556. — British preference, 559. — Preference in non-self-governing colonies, 561. — IV. Conclusions, 562. — Possibilities of international treatment, 565.